Blood transfusion compliance in children with transfusion-dependent Thalassemia - Rahmayani, Susanti; Cahyadi, Andi; Andarsini, Mia Ratwita; Arumsari, Diah Kusuma; Efendi, Ferry; Ugrasena, I Dewa Gede (Edelweiss Applied Science and Technology, 2025)
Children with transfusion-dependent thalassemia (TDTs) need regular blood transfusions and maintain a 9-10 g/dl hemoglobin level. Unfortunately, blood transfusion implied iron overload, characterized by increased serum ferritin levels and iron accumulation in the tissues and blood as serum ferritin. This study evaluated the differences in serum ferritin levels in children with TDTs who were compliant and non-compliant with transfusion based on transfusion compliance. The cross-sectional study evaluated children with TDTs (5-18 years). The child would come for routine blood transfusions every 2-6 weeks. Low blood compliance was defined as children with a hemoglobin level below 7.0 g/dL at least three times during the last ten visits. We evaluate ferritin levels every three months. We use the Chi-Square test with p<0.05 for the two-tail test. About 67 TDTs children met the criteria; 55.2% were male, and 56.2% were adolescents. The mean hemoglobin level was 7.9 (SD 0.47) g/dL. About 27 (30.3%) children had non-compliance, and 62(69.7%) were good compliance. About 51.9% of children come every two weeks for blood transfusions in the non-compliance group, and 64.5% come every four weeks in the good compliance group with p=0.038. The mean ferritin level in the non-compliance group was higher than good compliance: 2656.0 (1241.58) ng/mL compared to 2123.7 (SD 1231.61) ng/mL with p=0.027. Most children in non-compliance (51.9%) had serum ferritin levels above 2500 mg/dL, and 52.8% in good compliance had ferritin 1000-2500 ng/mL with p=0.024. Feritin level in children with TDT with non-blood transfusion compliance was higher than reasonable.